Comparison of microstructures and magnetic properties of Tb-Pr-Cu-Al and Tb-Nd-Cu-Al grain boundary diffused Nd-Fe-B magnets - Zixiang Mo; Qingzheng Jiang; Mengping Kan; Jianming Li; Hang Wang (Journal of Materials Research and Technology)
Low melting alloys containing heavy rare earth element Tb have been widely used for grain boundary diffusion (GBD) to increase the coercivity (Hcj) of sintered Nd-Fe-B magnets. The addition of Pr has been demonstrated to further enhance the coercivity for Tb-diffused magnets. With chemical properties similar to Pr, Nd can also substitute for Tb, contributing to a further reduction in heavy rare earth content in diffusion sources. However, the differences between Pr and Nd in influencing Tb diffusion behavior have not been fully explored. This paper systematically compared the magnetic properties and microstructure of TbxNd70-xAl20Cu10 (x = 10, 30, 50, 70, at%) and TbxPr70-xAl20Cu10 (x = 10, 30, 50, 70, at%) diffused magnets, with a focusing on the effects of Pr and Nd substitution on Tb diffusion depth, diffusion coefficient, and Tb content in the shell layer. After diffusion with Tb30Nd40Al20Cu10, the coercivity increased significantly from 15.87 kOe to 24.86 kOe, with a coercivity temperature coefficient of −0.491 %/°C at the range of 20–150 °C. Compared with TbxPr70-xAl20Cu10 diffused magnets, Tb shows greater diffusion depth and diffusion coefficient, along with a thick Tb-rich shell around the main phase grains in TbxNd70-xAl20Cu10 diffused magnet. However, for diffusion sources with low Tb content, Tb-Pr-Cu-Al diffused magnets exhibited superior coercivity due to the high Pr content in the main phase grains and the formation of continuous thin grain boundary layer.